THE INFLUENCE OF CULTURAL STRUCTURE TOWARD GENDER STEREOTYPES IN THE FILM FROZEN 2 BY JENNIFER LEE - Rahmasari, Aulya; Panggabean, Waladdin (Prologue: Journal on Language and Literature, 2025)
This study examines the influence of cultural structure on gender stereotypes in "Frozen 2" by Jennifer Lee, with two main objectives: 1) to identify the forms of gender stereotypes present and 2) to describe how these stereotypes are influence by cultural structures. Employing Karl Marx's cultural structure theory, the research examines the "base" through subcategories such as social class, ideology, and division of labor, as well as the "superstructure" encompassing laws, politics, culture, and art. Additionally, it incorporates Simone de Beauvoir's perspective on gender stereotypes, focusing on the concept of "the Other" with subcategories including intersectionality, stereotypes as tools for power, the eternal feminine, and the notion of going beyond women. Utilizing a qualitative methodology, the study conducts a descriptive analysis of the film alongside relevant literature. The findings reveal that "Frozen 2" portrays various gender stereotypes, particularly in its depiction of female characters who, despite their strength and independence, are still influenced by traditional gender norms. Ultimately, the research highlights how cultural structures significantly impact the representation of gender in the film, illustrating the complex interplay between societal norms and individual identity, and contributing to a deeper understanding of how cultural narratives can either reinforce or challenge gender stereotypes.